PENGARUH KONSENTRASI DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP PRESTASI BELAJAR IPS SISWA KELAS V SDN MANISREJO I KABUPATEN MAGETAN - Mallawi, Ibadullah; Tristiar, A.A (Premiere Educandum, 2013)
The goal of research to determin the relationship among concentration and critical thinking with learning achievement of grade V for the student SDN Manisrejo 1 Magetan. This research applies descriptive correlasional and expost facto method with quantitative approach. The population of this research consist of 33 student. The result of the analysis show that: (1) there is significant relationship between the concentration with learning achievement by t (2,564), (p) 0,016; (2) there is significant relationship between the critical thinking with learning achievement by t (2,063), (p) 0,048; and (3) there is significant relationship between the concentration and critical thinking with learning achievement by F (10,802), (p) = 0,000. Key words: Concentration, Critical Thinking, Learning Achievement